Argumentative discourse construction through the AREL framework in EFL university classrooms: A qualitative study - Asty Widyastuti; Endang Darsih; Diva Zahra Anindya (Cipta Pustaka Nusantara, 2026)
This study addresses the challenges faced by EFL university students in constructing coherent and logical spoken arguments in academic contexts. Despite the increasing emphasis on argumentative speaking in higher education, many learners struggle to organize ideas and provide sufficient justification during real-time communication. This study aims to explore how Indonesian EFL university students construct argumentative discourse using the AREL (Assertion, Reason, Evidence, Linkback) framework, identify the challenges they encounter, and examine their perceptions of its usefulness. A qualitative research design was employed involving five university students who participated in an argumentative speaking task followed by semi-structured interviews. The data were analyzed using thematic analysis. The findings indicate that students were able to use the AREL framework to structure their arguments more coherently; however, they experienced difficulties in generating relevant evidence, maintaining fluency, and managing cognitive load during spontaneous speaking. Despite these challenges, students perceived AREL as an effective framework that improved clarity and logical organization of their spoken arguments. These findings suggest that AREL can serve as a valuable pedagogical tool to support argumentative speaking development in EFL higher education contexts.